2010
DOI: 10.5539/elt.v3n1p166
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Burnout among Instructors Working at ESOGU Preparatory School

Abstract: Burnout is an issue to be taken seriously in the workplaces where human interaction is salient and very important. The aim of the research is to investigate burnout among the instructors working at ESOGU preparatory school and find out what factors affect their levels of burnout. 28 instructors working in this institution participated in the study. The results of the study showed that the only significant contributor of burnout among the instructors is their perceived level of stress at the workplace. Except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Similarly, several studies which specially focused on burnout experienced by EFL teachers at schools and universities (Cephe, 2010;Özkanal and Arıkan, 2010;Mukundan andKhandehroo, 2010 andÖztürk, 2013) also revealed the results that are in accordance with the results of the present study indicating that EFl teachers have different levels of burnout.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 91%
“…Similarly, several studies which specially focused on burnout experienced by EFL teachers at schools and universities (Cephe, 2010;Özkanal and Arıkan, 2010;Mukundan andKhandehroo, 2010 andÖztürk, 2013) also revealed the results that are in accordance with the results of the present study indicating that EFl teachers have different levels of burnout.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 91%
“…To this end, many studies have been done to detect the sources of burnout within the teaching profession. For example: age, gender, years of experience, level of education (Maslach & Jackson, 1981;Ozkanal, 2010); classroom environment (Dorman, 2003); decreased parent involvement, low physical activity (Colangelo, 2004), teacher's attitudes towards perceived stressors (Rodriguez, 2006), and personality traits (Schaufeli, 2003) have been found to influence teacher burnout.…”
mentioning
confidence: 99%
“…Unlike other studies, Karanfil and Yeşilbursa (2021) obtained very interesting findings as a result of their research. The findings of their studies revealed that single teachers reported higher levels of emotional exhaustion than their married or divorced colleagues opposing many studies in which marital status is unimportant (Atmaca, 2017;Özkanal & Arıkan, 2010;Kurtoğlu, 2011;Öztürk, 2013). In addition, teachers at state schools reported higher levels of emotional exhaustion than those at private schools, which is similar to the study conducted by Kimsesiz (2017).…”
Section: Discussionmentioning
confidence: 79%